Exploring the multifunctionality of myco-synthesized selenium nanoparticles: biological, docking study and plant growth-promoting perspectives - Sonbol, Hana; Ahmed, Eman Zakaria; Mohamed, Eslam T.; Abdelmonem, Asmaa F.; El-Sayed, Heba (Frontiers in Microbiology, 2025)
Selenium is a vital trace mineral that regulates essential physiological functions, and the development of sustainable methods for synthesizing selenium nanoparticles (SeNPs) is an active area of research. This study reported the mycosynthesis of SeNPs using the aqueous extract of the edible mushroom Pleurotus ostreatus. The synthesized SeNPs were characterized using various analytical techniques, including UV–visible spectroscopy, dynamic light scattering, transmission electron microscopy (TEM), and Fourier-transform infrared spectroscopy (FTIR). The results revealed that the SeNPs exhibited spherical morphology with a diameter range of 72–148 nm, moderate stability with a zeta potential of −10.5 mV, and a polydispersity index of 0.27. The myco-synthesized SeNPs demonstrated potent antioxidant activity with a DPPH radical scavenging IC50 value of 662.1 ± 1.05 μg/mL, comparable to the standard antioxidant Trolox (IC50 = 24.42 ± 0.87 μM). Furthermore, SeNPs exhibited considerable antimicrobial efficacy against Staphylococcus aureus (17 ± 0.02 mm inhibition zone), followed by Escherichia coli (16 ± 1.04 mm) and Candida albicans (12 ± 0.3 mm). Additionally, SeNPs displayed moderate antiviral activity against a low-pathogenic coronavirus (229E) strain, with a selectivity index (SI) of 5. In agriculture, the application of SeNPs at 10 μM significantly increased primary metabolite production in wheat (Triticum aestivum), with total soluble sugars reaching 54.32 mg/g and soluble proteins increasing to 139.66 mg/g, promoting both shoot and root growth. The comprehensive characterization and evaluation of SeNPs provide valuable insights into their multifunctionality, paving the way for further exploration in medicine, agriculture, and environmental applications.